2015
DOI: 10.1111/cid.12330
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Healing at Implants with Different Configuration and Modified Surfaces: An Experimental Study in the Dog

Abstract: The two implant systems used resulted in similar osseointegration after 1 and 2 months of healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…,b; Schweikert et al. ). These studies confirmed differences in the rates of bone apposition and the extent of osseointegration.…”
mentioning
confidence: 99%
“…,b; Schweikert et al. ). These studies confirmed differences in the rates of bone apposition and the extent of osseointegration.…”
mentioning
confidence: 99%
“…In general terms one can say that the system ICX Active is a range of implants using elements of micro-threads -ICX Premium, and slim implants Slim Boy for the given slim type of alveolus, and it also uses anchoring of supra-structures without threads, which is a highly advantageous element against peri-implantitis. The ICX system uses anti-rotational elements and elements of a self-locking angle in connection of the supra-structure, which reduces or prevents bacteria colonisation and thus peri-implantitis [14,15]. The systems Ankylos, Astra Tech have similar elements.…”
Section: Discussionmentioning
confidence: 99%